1986
DOI: 10.1007/bf00243834
|View full text |Cite
|
Sign up to set email alerts
|

Afferent and efferent connections of striatal grafts implanted into the ibotenic acid lesioned neostriatum in adult rats

Abstract: The afferent and efferent connections of grafts of fetal caudate-putamen, implanted into the ibotenic acid (IA)-lesioned striatum of adult rats, have been studied with wheat germ agglutinin conjugated horseradish peroxidase (WGA-HRP) as a combined retrograde and anterograde tracer, and with aldehyde fluorescence histochemistry for the visualisation of dopamine-containing nigrostriatal afferents from the host. The WGA-HRP was deposited in crystalline form (within a capillary tip) either into the depth of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In animal models, the proposed mechanisms of transplant-induced improvement observed include graft-derived transmitter release as well as the production of trophic factors (11,13,16,(43)(44)(45)(46). Previous animal studies have demonstrated reconnection of the cortical, thalamic and dopaminergic system with implanted fetal striatum (12,13,40,47). We demonstrate here that host neuronal systems that normally project to the striatum (for example dopaminergic neurons) can grow into the human striatal tissue grafts.…”
Section: Discussionmentioning
confidence: 60%
“…In animal models, the proposed mechanisms of transplant-induced improvement observed include graft-derived transmitter release as well as the production of trophic factors (11,13,16,(43)(44)(45)(46). Previous animal studies have demonstrated reconnection of the cortical, thalamic and dopaminergic system with implanted fetal striatum (12,13,40,47). We demonstrate here that host neuronal systems that normally project to the striatum (for example dopaminergic neurons) can grow into the human striatal tissue grafts.…”
Section: Discussionmentioning
confidence: 60%
“…Preclinical rodent and primate experiments demonstrated the feasibility of using embryonic striatal grafts for the treatment of HD. Fetal striatal grafts survive (5), induce behavioral recovery (6,7), and establish connectivity with the rodent brain (8,9). Similar results have been reported with xenografts of porcine and human striatal tissue into rodents (2,(9)(10)(11)(12).…”
mentioning
confidence: 54%
“…Groves et al, 2003) we were interested particularly in the development of the striatal neurotoxic lesion during a longer time frame. Surprisingly, the studies referring to long-term experiments are less frequent (Isacson et al, 1985;Pritzel et al, 1986;DiFiglia et al, 1988;Liu et al, 1990;Wictorin, 1992) and have not dealt with detailed histopathological characteristic of the progression of neurodegenerative process.…”
Section: Introductionmentioning
confidence: 96%